O direito e sua normatividade em John Finnis: uma exposição e defesa da teoria da lei natural contra o ceticismo e o eliminativismo - Thiago dos Santos Luz (2024)
One of the main challenges of contemporary legal philosophy is understanding how practical reasoning works and how law relates to it. In this context, this dissertation seeks to explain law and its ability to provide reasons for action in accordance with the neoclassical natural law theory subscribed by John Finnis, in addition to refute a recent skeptical and eliminativist doctrinal trend in relation to law and its normativity. To this end, a deep and systematic analysis was carried out not only of the book Natural Law and Natural Rights (NLNR) – a reference work that concentrates the core of Finnis' natural law thinking – but also of several other writings produced by the author throughout his extensive academic career, including Aquinas and the Collected Essays. Work was carried out to identify and articulate the fundamental propositions of the ethical, political and legal theories that make up Finnis' doctrine of natural law, often scattered in complex and long texts, produced in a language not always accessible or readily assimilated by those least accustomed to tradition. In the midst of this, the exhibition was gradually enriched, depending on the subject covered, with important theoretical subsidies offered by other thinkers, with emphasis on Joseph Raz's theory of normativity. In this way, the care for accurancy and fidelity in the presentation of Finnis’ theory on the normativity of law and the ethical and political bases that support it did not prevent an exegetical activity to grasp it to its fullest extent. In contrast to the natural law vision exposed in the first part of the work, some contemporary initiatives that propose the abandonment of the doctrinal concept of law and deny or underestimate legal normativity were the subject-matter of attention in the sequence. The ideas developed in four scientific articles, selected as representative of this line of thought, were exposed: Does Law ‘Exist’? Eliminativism in Legal Philosophy, by Hillary Nye; The End of Jurisprudence, by Scott Hershovitz; Doing Without the Concept of Law, by Lewis Kornhauser, and; Is General Jurisprudence Interesting?, by David Enoch. While Nye, Hershovitz and Kornhauser proclaim themselves ‘eliminativists’, Enoch is quite skeptical about the normativity of law, equating it to that of a simple board game. Then follows a separate chapter housing a critical analysis of the skeptical and eliminativist claims formulated by these authors, based on the adoption, as a paradigm, of Finnis' natural law theory. The conclusion, in the end, is that the latter is sound and consistent, to a sufficient degree to prevail over the former.